ChemInform Abstract: NHC Catalyzed Direct Addition of HMF to Diazo Compounds: Synthesis of Acyl Hydrazones with Antitumor Activity. Issue 6 (February 2015) - Antonio, Joao P. M.; Frade, Raquel F. M.; Santos, Fabio M. F.; Coelho, Jaime A. S.; Afonso, Carlos A. M.; Gois, Pedro M. P.; Trindade, Alexandre F.
Abstract A direct access to an unexplored family of 5‐hydroxymethylfurfural (HMF)‐based acylhydrazones displaying antitumor activity is given.